First person - Patricia Shaw (The Company of Biologists, 2020)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms, helping early-career researchers promote themselves alongside their papers. Patricia Shaw is first author on 'Longitudinal neuroanatomical and behavioral analyses show phenotypic drift and variability in the Ts65Dn mouse model of Down syndrome', published in DMM. Patricia is a PhD student in the lab of Tarik Haydar at Boston University School of Medicine, USA, researching the underlying genetic and cellular mechanisms that contribute to brain development, and investigating how these processes are altered in diseases and disorders, such as Down syndrome, in order to identify novel targetable approaches for therapeutics.